2002
DOI: 10.1038/sj....bjc.6600189...
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polyol accumulation in a new ovarian carcinoma cell line, CABA I: a1H NMR study

Abstract: Ovarian carcinomas represent a major form of gynaecological malignancies, whose treatment consists mainly of surgery and chemotherapy. Besides the difficulty of prognosis, therapy of ovarian carcinomas has reached scarce improvement, as a consequence of lack of efficacy and development of drug-resistance. The need of different biochemical and functional parameters has grown, in order to obtain a larger view on processes of biological and clinical significance. In this paper we report novel metabolic features d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Although no reports are available on the quantities of non-protein thiols, protein thiols, non-protein disulfides, and protein disulfides in OVCAR-3 cells, the quantity of GSH determined to be 12.16±0.05 nmol/million cells before reduction in non-protein thiol samples by this method (Table 1) is in agreement with the literature reported values for the cells, which are between 7.9±1.3 nmol/million cells [34] and 29.5 nmol/million cells [35]. …”
Section: Resultssupporting
confidence: 91%
“…Although no reports are available on the quantities of non-protein thiols, protein thiols, non-protein disulfides, and protein disulfides in OVCAR-3 cells, the quantity of GSH determined to be 12.16±0.05 nmol/million cells before reduction in non-protein thiol samples by this method (Table 1) is in agreement with the literature reported values for the cells, which are between 7.9±1.3 nmol/million cells [34] and 29.5 nmol/million cells [35]. …”
Section: Resultssupporting
confidence: 91%
“…Cells were washed twice with ice-cold physiologic saline solution and pellets resuspended in 0.5 mL ice-cold twice-distilled water. Aqueous extracts (20 Â 10 6 -30 Â 10 6 cells/sample) were prepared in ethanol/H 2 O (70:30, v/v) according to an established protocol already described (17,24,25). This method was proven to be as efficient as the more commonly used extraction in perchloric acid, with the additional advantages of higher procedural simplicity (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution NMR experiments (25jC) were done at either 400 or 700 MHz (Bruker AVANCE spectrometers, Karlsruhe, Germany). 1 H NMR spectra of cell extracts were obtained using acquisition pulses, water presaturation, data processing, and data analysis as described already (17). Quantification of individual metabolites was obtained from peak areas using correction factors determined by experiments at the equilibrium of magnetization (90j pulses, 30.00-second interpulse delay).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion in minositol has been previously detected in several studies, 27,46,53 and such variation was assigned to several possible causes: disturbance in its osmolytic function through drug-induced partial inhibition of the Na + /m-inositol cotransporter (SMIT); 46 diminished inhibition of the mitogen-activated protein kinase (MAPK) signal transduction pathway, thus leading to stimulation of cells into apoptosis; 46 effect on the biosynthesis and turnover of some phospholipids; 54 or activation of cell detoxification processes. To clarify the role of inositols in treated MG-63 cells (particularly upon cDDP and DOX treatments), STOCSY analysis of the inositol resonances (not shown) revealed that, in cDDP-treated cells, m-inositol decreases concomitantly with Tau, Glu/Gln, and creatine (besides sinositol), whereas in DOX-treated cells, m-inositol decreases together with Glu/Gln and GSH (and s-inositol).…”
Section: Nucleotides and Other Compoundsmentioning
confidence: 99%